Hollow Façades: constructing the edit of Built to Scale - Seah, Sean Pang Boon (Nanyang Technological University, 2023)
This report details the creative approaches and development behind the short film, Built to Scale, from the perspective of the co-editor role. The first section recounts experiences of curating specific influences and assets during pre-production in tandem with the writer-director to craft a compelling tale. Guided by the clarity afforded by research, the following section chronicles the film’s progress to achieve its thematic identity amidst shifting circumstances during production, before delving into post-production workflows and the collaborative efforts to shape the cut and achieve its intended vision. Finally, this report concludes with a reflection on the struggles and triumphs in executing this editorial feat, alongside general thoughts on the author’s involvement in the project.